Karma Tokens – A Framework to Systematically Measure and Offset ESG Debt and Enable Unbiased Governance for Responsible & Sustainable Growth - Jeremiah, Namitha (Digital Repository of Theses, 2025)
Context One of the primary drivers of climate change is trapped CO2 that is released into the atmosphere by conventional energy sources like coal and petroleum. India still uses a lot of fossil fuels; despite the fact that "clean" and "renewable" energy technology have advanced significantly. In order to ascertain why the G20 nations—particularly India—are not meeting the objectives of the Paris Agreement, the worldwide strategy to mitigate climate change, this study has embarked on a journey of data collection, analysis, and hypothesis testing based on Business Responsibility and Sustainability Reporting (BRSR) published by the Government of India. The phrase "ESG debt" was coined as part of this study to describe an entity's adverse environmental effects and to provide guidance on how to mitigate them. Furthermore, the key objective of this research is a novel implementation framework termed "Karma tokens". Karma Token formulates a set of guidelines to incentivize companies and individuals to become more conscious of their actions and behaviors in relation to their carbon footprint. The research on "ESG Debt & Karma Tokens" investigates the social cost of emissions, the time-value of carbon, and carbon pricing schemes. Through the use of Karma Tokens, this framework seeks to increase public awareness and encourage sustainable growth in order to enhance both the planet's and people's quality of life. Research Methods The study recommends using positivism and pragmatism as its research philosophies in conjunction with the Theory of Inventive Problem Solving (TRIZ theory) to find answers for the research questions, taking into account the necessity of empirical data analysis based on emissions data, and maintaining a practical point of view while drawing inferences from the analysis. This study used a mixed-method approach, combining the advantages of qualitative and quantitative analysis. The data sources include a combination of primary and secondary data analysis, case studies, and survey research. To meet the research's objective, Julius, an AI-powered tool for statistical data processing, linear regressions, correlation analysis, descriptive statistics, and projections for data analytics and corroboration, is employed. In order to do an empirical investigation and create a strategy to arrive at an effective carbon price, this study investigated data samples of emissions and the social cost of carbon to compute ESG debt. Results This research examines India’s path to net-zero emissions by 2070, emphasizing the critical role of industry-level emissions and the potential of ESG frameworks in accelerating climate action. Analysis of BRSR data from India’s top 100 companies reveals that heavy engineering sectors—responsible for 88% of emissions among high-turnover firms—have shown slow progress, with only 34% achieving notable reductions in FY24 and renewable energy usage remaining at just 1%. In contrast, non-engineering sectors demonstrate higher renewable integration (73%) and lower emissions intensity, indicating faster decarbonization potential. Strong correlations between GDP, energy supply, and emissions (>0.98) confirm that India’s economic growth remains tightly coupled with carbon output. The study proposes an ESG debt model leveraging BRSR disclosures to quantify environmental, social, and governance liabilities. This model, supported by technologies like AI, blockchain, and IoT, can dynamically track emissions and financial impacts. It integrates carbon pricing mechanisms using the Social Cost of Carbon (SCC) and recommends offsets through CSR initiatives. Financial instruments such as green bonds and sustainability-linked loans further reinforce the economic case for emissions reduction. The findings highlight that widespread ESG adoption, sector-specific policy reforms, carbon markets, and targeted incentives are essential to align industrial growth with India’s climate goals. Discussion and Conclusions This research highlights the pressing misalignment between India’s current industrial emissions trajectory and its 2070 net-zero ambitions. The heavy engineering sector, with its high emissions intensity and minimal renewable energy integration, remains a critical challenge. In contrast, non-engineering sectors show promising signs of transition, demonstrating the feasibility of decarbonization when accountability, incentives, and policy alignment converge. The ESG debt framework introduced here offers a novel, quantifiable mechanism to measure sustainability performance. By integrating ESG liabilities with carbon pricing metrics like the Social Cost of Carbon (SCC), the model creates financial motivation for companies to internalize environmental costs and adopt cleaner technologies. Supported by real-time tracking technologies and predictive analytics, ESG debt can serve as both a corporate performance metric and a policy planning tool. While green finance instruments and carbon markets present enabling mechanisms, their limited adoption underscores the need for regulatory reinforcement and broader ESG literacy. Sector-specific mandates, especially stricter decarbonization targets for heavy industries and earlier net-zero pathways for others, will be essential. In conclusion, ESG debt transforms sustainability into a strategic imperative. If scaled effectively, it can realign India’s industrial growth with climate responsibility—turning net-zero from a distant aspiration into a structured, accountable, and achievable goal.